Leider Ohne Worte Fur Pianoforte Un Violin - BARTHOLDY'S (C.F Peters)
1. OP. 19 No. 1 E Dur - Mi Majeur - E Major,2, OP. 19 no.2 A Moll - La Mineur - A Minor, OP.19 n0. 3 A Dur La Majeur- A. Major, 4. Op. 19 No 4 A Dur -La Majeur- A Major 5, 5. OP.19 No. 5 Fis Moll Fa Diese Maneur F# Minor, 6. Op. 19 no.6 G Moll -Sol Mineur- G Minor